Technical paper on socioeconomics and food security dimensions of climate change - Ringler, Claudia; Rosegrant, Mark W. (African Group of Negotiators Experts Support, 2020)
This paper examines the economic and food security implications of climate change in Africa with a focus on population and income growth, agricultural livelihoods and food security, and the role of gender and youth. Food security impacts include climate change risks to food production and agricultural value chains in Africa. The paper then identifies key entry points to address climate change and socioeconomic challenges, including the role of investment in agricultural research, irrigation investment, climate-smart agriculture, the role of ICT, trade as a buffer to climate change, crop insurance, as well as safety nets for the poorest and most vulnerable.